2021
DOI: 10.3390/su13031216
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Media in the Luxury Tourism Business: A Research Review and Trajectory Assessment

Abstract: The luxury tourism industry immediately conjures up thoughts of exclusivity, with access to it confined to a small and elite group of travelers often located within their own social bubble. Our systematic literature review seeks to understand how tourism scholarship has addressed the issue of luxury travel based on social media pronouncements and the areas of concentration in which earlier studies have been conducted. Literature was sourced using the following key terms “luxury tourism”, “elite travel”, “socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The underpinning factors comprising the hierarchy of LTNs provide an important direction toward understanding, promoting and predicting tourism trends. Luxury is an important feature in developing a tourism product and this can benefit luxury tourism providers by giving attention to developing strategies and carefully planning the content of video advertisements (Thirumaran et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The underpinning factors comprising the hierarchy of LTNs provide an important direction toward understanding, promoting and predicting tourism trends. Luxury is an important feature in developing a tourism product and this can benefit luxury tourism providers by giving attention to developing strategies and carefully planning the content of video advertisements (Thirumaran et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Berhanu and Raj’s (2020) study suggest that there has been a shift in the luxury travel market, from the traditional rich to younger demographics who are heavy SM users. Thirumaran et al (2021) focused on exploring SM and tourism and identified two key findings. First, how SM is associated with a sustainable approach to luxury travel.…”
Section: Luxury Travelmentioning
confidence: 99%
“…This is also relevant in relation to specific targets, where Millennials and Generation Z people are a growing market segment (Deloitte, 2018). This paper departs from the understanding of the relevance of social media in luxury tourism (see Thirumaran et al, 2021) to the development of a co-created relationship between businesses and customers (Leung et al, 2017;Wu & Gao, 2019). According to Harkison (2018), who studied the luxury accommodation sector, 'active interaction between a company and a customer creates value, and this value is centred on the customer's experience ' (p.11).…”
mentioning
confidence: 93%
“…Tourism systematic literature reviews provide insights into research topics, theories, methods and potential gaps (Brendel et al , 2020). Scholars intend to review tourism research based on the specific field and period: luxury tourism (Iloranta, 2022; Thirumaran et al , 2021), live tourism (Lin et al , 2022), smart tourism (Hamid et al , 2021; Shafiee et al , 2021) and sustainable tourism (Santos et al , 2021). Reviewing precious tourism literature review articles published in English Web of Science (WOS) and Chinese China National Knowledge Infrastructure (CNKI) language journals has yet to be conducted.…”
Section: Introductionmentioning
confidence: 99%